2021
DOI: 10.31083/j.jin2002028
|View full text |Cite
|
Sign up to set email alerts
|

The connection between rs6265 polymorphism in the BDNF gene and successful mastering of the video-oculographic interface

Abstract: A video-oculographic interface is a system for controlling objects using eye movements. The video-oculographic interface differs from other brain-computer interfaces regarding its improved accuracy, simplicity, and ergonomics. Despite these advantages, all users are not equally successful in mastering these various devices. It has been suggested that the genetic characteristics of the operators may determine the efficiency of video-oculographic interface mastery. We recruited healthy users with rs6313, rs20303… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Finally, the paper by Turovsky et al [11] analyses the relationship between the genetic characteristics of healthy subjects and success in performing a sensory-motor task that consists of using a video-oculographic interface (i.e., control of a virtual marker via eye movements from a start to a goal-point bypassing obstacles). The authors found an association between task performance and variants in the brain-derived neurotrophic factor (BDNF) gene, which has been implicated in synaptic plasticity, working memory, and long-term potentiation.…”
mentioning
confidence: 99%
“…Finally, the paper by Turovsky et al [11] analyses the relationship between the genetic characteristics of healthy subjects and success in performing a sensory-motor task that consists of using a video-oculographic interface (i.e., control of a virtual marker via eye movements from a start to a goal-point bypassing obstacles). The authors found an association between task performance and variants in the brain-derived neurotrophic factor (BDNF) gene, which has been implicated in synaptic plasticity, working memory, and long-term potentiation.…”
mentioning
confidence: 99%